Near-infrared absorbing semitransparent organic solar cells - Meiss, J; Holzmueller, F; Gresser, R; Leo, K; Riede, M (American Institute of Physics, 2011)
We present efficient, semitransparent small molecule organic solar cells. The devices employ an indium tin oxide-free top contact, consisting of thin metal films and an additional organic capping layer for enhanced light in/outcoupling. The solar cell encorporates a bulk heterojunction with the donor material Ph2-benz-bodipy, an infrared absorber. Combination of Ph2-benz-bodipy with C60 as acceptor leads to devices with high open circuit voltages of up to 0.81 V and short circuit current densities of 5–6 mA/cm2, resulting in efficiences of 2.2%–2.5%. At the same time, the devices are highly transparent, with an average transmittance in the visible range (400–750 nm) of up to 47.9%, with peaks at 538 nm of up to 64.2% and an average transmittance in the yellow-green range of up to 61.8%. © 2011 American Institute of Physics.